PENENTUAN HARGA OPSI SAHAM DENGAN MENGGUNAKAN METODE BEDA HINGGA CRANK-NICHOLSON (C-N) - OKI TJANDRA SURYA KURNIAWAN (E-Jurnal Matematika, 2012)
An option is a contract to buy or sell a specific financial product officially known as the option's underlying instrument. For equity options, the underlying instrument is a stock or similar product. An option establishes a specific price, called the strike price, at which the contract may be exercised, and it has an expiration date. Options come in two varieties, calls and puts.  The right to buy a stock at a specific price is called a call and the right to sell a stock at a specific price is called a put.  To price an option one may use Black-Scholes formula which is solved analytically and numerically. In this project numerical solution using Crank-Nicolson finite difference method is demonstrated. The purpose of this project is to study how Crank-Nicolson different from explicit and implicit methods. The result shows that Crank-Nicolson method gives higher prices than explicit and implicit methods. In terms of calculation, explicit method  is much simpler than the other two methods.